FACTORS INFLUENCING DESTINATION IMAGE FORMATION IN DISTANT CULTURE COUNTRIES: the moderating role of familiarity, corporate image and travel motivations. - Pérez-Tapia, Gema (My University, 2017)
The present research aims to explain more deeply the Theory of the Image of Tourist Destination and its process of formation, specifically regarding the factors that influence the above-mentioned process. This work tries to develop and empirically validate a model which explains the main factors that influence the image of a tourist destination and its process of formation. Based on a literature review, this will involve analysing the relationship between the different components of the perceived image. These include the familiarity, the corporate image and the motivation of potential tourists.
Keywords: Turismo; Tourism; Destination image; Distant culture countries